Religion on the island of Ireland during the COVID-19 pandemic: piety in the public sphere? - Ganiel, Gladys (Religion, state & society, 2025)
This article examines how religious institutions and religious media on the island of Ireland framed religion’s place in the public sphere during COVID-19. Through qualitative analysis of Catholic, Protestant, Muslim, and Humanist organisations’ public documents and religious media, it finds religious institutions supported government restrictions and adopted secular reasoning to justify their actions. The major churches also avoided claiming special status or religious freedom protections. This reveals a constrained religious input to public debates, reflecting a realistic assessment by religious leaders that they lack policy influence due to long-term declines in church power. The pandemic provides evidence of a reformulation of the relationships between religion, state, and society on the island, albeit with religion retaining more influence in Northern Ireland. Religious media outlets largely reproduced institutional discourses, with the exception of a weekly newspaper, the Irish Catholic. The Irish Catholic argued that stringent restrictions in the Republic of Ireland violated religious freedom, and made a case for the value of piety in the public sphere. But while religious actors still seek to contribute to public debates, there is little consensus or vision about religions’ distinctive contributions, even around existential questions posed by the pandemic.